Born Globals in Poland: Development Factors and Research Overview - Pilarska, Czesława; Wałęga, Grzegorz (Central and Eastern European Economic Review, 2020)
Objective: This paper investigates the concept of the born global, indicates the main attributes and sources of success for enterprises that internationalised early, and demonstrates the scale of the born global phenomenon in Poland. Research Design & Methods: A review of empirical studies is the research method used in the paper. Secondary data from research studies is collected. The article outlines the theoretical background of born globals. A brief overview of the existing research (since 2004) is also provided. The results are compiled to demonstrate the scale of the born global phenomenon in Poland. Findings: A review of quantitative research indicates that the percentage of born globals in Poland can be estimated at 30–50% of all SMEs which are engaged in international activities. Polish managers have the necessary knowledge and traits for early internationalisation; the primary factors limiting the development of born global are limited financial and organisational resources. Implications/Recommendations: The existing quantitative analyses of born globals do not sufficiently enable the factors that constitute the main barriers to the development of this sector in Poland to be identified. There is still a room to plan the appropriate support policies for SMEs on international markets. Contribution: This paper addresses mainstream research on born globals, which are part of broader trends in the modern economy. This new generation of small and medium-sized enterprises, just as economic globalisation, the opening of markets and acceleration in the field of ICT development, is particularly relevant to both developing countries and middle-income economies such as Poland.